Use of Mineral Weathering Bacteria to Enhance Nutrient Availability in Crops: A Review - Ribeiro, Igor Daniel Alves; Volpiano, Camila Gazolla; Vargas, Luciano Kayser; Granada, Camille Eichelberger; Lisboa, Bruno Brito; Passaglia, Luciane Maria Pereira (Frontiers in Plant Science, 2020)
Rocks and minerals are potential sources of low-cost nutrients for crop production. However, the low solubility of minerals is an obstacle to the widespread use of rock powders as direct fertilizers. This problem could be overcome by using the biological weathering process. It is an interaction between minerals and rocks, plants, and bacteria that results in the release of macro- and micronutrients into the soil solution. Plants are important agents in this process. They act directly in the mineral dissolution or sustain a wide diversity of weathering microorganisms in the root environment. Such microorganisms promote mineral dissolution by producing complexing ligands (siderophores and organic acids), which affect pH (via organic or inorganic acid production), or perform redox reactions. A wide variety of rhizosphere microorganisms could also promote plant development, contributing to the weathering activity directly performed by plants. The inoculation of weathering bacteria in soil or plants, especially combined with use of crushed rocks, can improve crop production and increase soil fertility. This approach is more sustainable than conventional fertilization practices. It importantly contributes to the reduction in climate change linked to agricultural activity. Besides, it could lower the dependency on imported fertilizers, thus improving local development.